Pengaruh Pajak Daerah, Retribusi Daerah, Dana Alokasi Umum, Dana Alokasi Khusus, Dan Pertumbuhan Ekonomi Terhadap Pengalokasian Belanja Modal (Studi Empiris pada Pemerintah Kabupaten/Kota Di Jawa Tengah periode 2012-2014). - Hasbullah, Rifqi Noveandra, Drs. Yuli Tri Cahyono , M.M., Akt., CA (2017)
The study aimed at providing empirical evidence and finding out the effect of local tax, local reribution,general alocation fund, specific alocation Fund, and economic growth on the allocation of capital expenditure budget by considering all data collection. The sample in this study is 105 districts/cities in Central Java from the years 2012-2014. The method uses is saturated sampling techniques, when members of all populations are used as samples. Analysis tool using classical assumption test and multiple regression analysis. The result of this research shows that local tax have influence on capital expendiuture Allocation, but local reribution, general alocation fund, Specific alocation fund, and economic growth not have influence on capital expenditure alocation. Keywords: local tax, local reribution,general alocation fund, specific allocation fund, economic growth and capital expenditure.